2004
DOI: 10.2527/2004.8282392x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a novel carbohydrate and protein source on sow performance during lactation12

Abstract: Ninety-one primiparous and multiparous sows and their pigs were used to evaluate the effects of a novel carbohydrate- and protein-based feed ingredient (Nutri-Pal, NP) on sow and litter performance during lactation. Nutri-Pal is a feed supplement for sows that consists of a blend of milk chocolate, brewer's yeast, whey products, and glucooligosaccharides. The dietary treatments consisted of a corn-soybean meal control and a corn-soybean meal plus 5% NP fed from d 110 of gestation to weaning. The diets were for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Therefore, there has been considerable research to identify factors that enhance the composition and yield of sow milk (Benzoni et al, 2012;Jang et al, 2013). Payne et al (2004) showed that sows fed a 5% NP (novel carbohydrate-and protein-based feed ingredient) diet, beginning on d 110 of gestation, were heavier at weaning than those fed a control diet, whereas there was no difference in weight at d 110 of gestation or d 1 post-farrowing between the treatment groups. However, these results do not agree with those of Johnston et al (2003), who reported that sows fed a diet containing 4% sucrose and 2% milk chocolate product had similar body weights at weaning as control sows.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there has been considerable research to identify factors that enhance the composition and yield of sow milk (Benzoni et al, 2012;Jang et al, 2013). Payne et al (2004) showed that sows fed a 5% NP (novel carbohydrate-and protein-based feed ingredient) diet, beginning on d 110 of gestation, were heavier at weaning than those fed a control diet, whereas there was no difference in weight at d 110 of gestation or d 1 post-farrowing between the treatment groups. However, these results do not agree with those of Johnston et al (2003), who reported that sows fed a diet containing 4% sucrose and 2% milk chocolate product had similar body weights at weaning as control sows.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, supplemental energy has been supplied by carbohydrates (corn starch) to provide isocaloric treatments, and feeding carbohydrates has not altered sow body condition, milk production and composition, or resulted in an increased piglet survival rate (Coffey et al., 1987; Payne et al., 2004). In this study, feeding of isocaloric diets with different glucose levels did not affect the body weight of sows, whereas the loss of backfat thickness was decreased when extra glucose was added in the diets during lactation.…”
Section: Discussionmentioning
confidence: 99%